The Correlation between Glycemic Control and Microvascular Complications in Type 1 Diabetes Mellitus Patients : Glycemic Control and Microvascular Complications in Type 1 Diabetes Mellitus Patients - Memon, Yasra; Fareed, Ghulam; Qureshi, Kamran Ali; Kumar, Mahesh; Baig, Muhammad Sohail; Memon, Zaheer Hussain; Karim, Imran (Pakistan Journal of Health Sciences, 2025)
Type 1 Diabetes Mellitus (T1DM) is a chronic condition that destroys pancreatic beta cells, leading to persistent hyperglycemia. Prolonged high levels resulted in an increased risk of microvascular complications. Glycemic control, indicated by HbA1c, plays a critical role in reducing these risks. Objective: To examine the strength of the relationship between HbA1c levels and the severity of microvascular complications in individuals with T1DM. Methods: A cross-sectional study was conducted on 30 patients with T1DM at Liaquat University Hospital, Hyderabad, from December 2024 to February 2025. HbA1c levels were recorded, and microvascular complications were evaluated using KDIGO criteria for nephropathy, ETDRS for retinopathy, and TCNS for neuropathy. Data were analyzed using descriptive statistics and inferential methods, including Spearman’s correlation and linear regression, through SPSS version 22.0. Results: The average age of participants was 24.23 ± 3.45 years, with a mean HbA1c level of 7.65 ± 1.15%. Retinopathy was the most frequent complication (73.3%), followed by neuropathy (63.3%) and nephropathy (40%). Combined complications were present in 40% of cases. HbA1c levels were significantly correlated with the severity of all microvascular complications, showing positive associations with KDIGO (r=0.839), ETDRS (r=0.864), and TCNS (r=0.870). HbA1c values also progressively increased with complication severity (p<0.001). Conclusions: It was concluded that poor glycemic control was strongly associated with the presence and severity of microvascular complications in T1DM patients. These findings highlight the importance of maintaining optimal HbA1c levels to mitigate complications. Further longitudinal studies are warranted to explore these associations in greater depth.